Genome Comparison of Erythromycin Resistant Campylobacter from Turkeys Identifies Hosts and Pathways for Horizontal Spread of erm(B) Genes - Florez-Cuadrado, Diego; Ugarte-Ruiz, María; Meric, Guillaume; Quesada, Alberto; Porrero, M. C.; Pascoe, Ben; Sáez-Llorente, Jose L.; Orozco, Gema L.; Domínguez, Lucas; Sheppard, Samuel K. (Frontiers in Microbiology, 2017)
Pathogens in the genus Campylobacter are the most common cause of food-borne bacterial gastro-enteritis. Campylobacteriosis, caused principally by Campylobacter jejuni and C. coli, is transmitted to humans by food of animal origin, especially poultry. As for many pathogens, antimicrobial resistance in Campylobacter is increasing at an alarming rate. Erythromycin prescription is the treatment of choice for clinical cases requiring antimicrobial therapy but this is compromised by mobility of the erythromycin resistance gene erm(B) between strains. Here we evaluate resistance to six antimicrobials in 170 Campylobacter isolates (133 C. coli and 37 C. jejuni) from turkeys. Erythromycin resistant isolates (n=85; 81 C. coli and 4 C. jejuni) were screened for the presence of the erm(B) gene, that has not previously been identified in isolates from turkeys. The genomes of 2 positive C. coli isolates were sequenced and in both isolates the erm(B) gene clustered with resistance determinants against aminoglycosides plus tetracycline, including aad9, aadE, aph(2")-IIIa, aph(3´)-IIIa and tet(O) genes. Comparative genomic analysis identified identical erm(B) sequences among Campylobacter from turkeys, Streptococcus suis from pigs and Enterococcus faecium and Clostridium difficile from humans. This is consistent with multiple horizontal transfer events among different bacterial species colonizing Turkeys. This example highlights the potential for dissemination of antimicrobial resistance across bacterial species boundaries which may compromise their effectiveness in antimicrobial therapy.